Impact of placenta praevia on obstetric outcome - Meena, Neelam; Dave, Anupama; Meena, Shivraj; Meena, Asha; Shrivastava, Ankita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Placenta praevia is the implantation of the placenta partially or totally in the lesser segment of the uterus. The blood loss is generally mild and frequent but at times can be enormous and life threatening. The frequency of placenta praevia is 3-5 per 1000 pregnancies thought out the world and is still increasing for the reason that of growing caesarean section rates.2 The present study was carried out to asses impact of placenta praevia on obstetric outcome at our setup. Methods: This was case control study that was conducted at department of gynaecology and obstetrics, M Y hospital, M G M medical college, Indore from Sep 2011 to Feb 2013. A predesigned proforma was used to collect the study variables. Results: The incidence of placenta previa was 0.76 %. Maximum patients belonged to age group of 21-30 years (70.43%) and in gravidae >2 (35.65%). In this study 22.6% patients of PPH, 36.52% of perpueral sepsis, 1.75% of UTI, 4.35% of ARF, 5.22% of wound infection, 1.74% of DIC and 5.22% patients of placenta accrete. Caesarean hysterectomy and uterine artery ligation were done in 6.08% and 13.04% patients respectively. Hysterectomy was done in 4 patients belonging to anterior PP and 3 patients in posterior PP group. Major placenta praevia was present in 47.82% patients. 6% patients present in hospital with gestational age <28 weeks. Low birth weight (<2.5 kg) baby was 65.21%. 2.86% patient of APH, 0.76% of PP, 1.40% of AP and 0.70% of UC. Conclusions: It was concluded that increased maternal age and parity, history of previous caesarean section are identified risk factors which are same as reported in western literature. Sonographic determination of the placental position where its location be-Neath the uterine incision is very important to predict maternal outcomes in placenta praevia patients, and such cases, close attention should be paid for massive haemorrhage.